The Influence of Work Motivation, Work Discipline, and Work Environment on the Performance of Employees in the Production Division of UD. Suwarlandono Art - Nirmalasari, Nirmalasari; Santoso, Bowo (Majapahit Journal of Islamic Finance and Management, 2025)
The era of globalization demands companies to boost competitiveness by optimizing human resources. Employee performance is a key factor in achieving organizational goals, influenced by work motivation, work discipline, and work environment. This study aims to analyze the effect of work motivation, work discipline, and work environment on the performance of employees in the production department of UD. Suwarlandono Art. The research method uses a quantitative approach with Partial Least Squares (PLS) analysis. The population in this study was 50 employees in the production department of UD. Suwarlandono Art, which was also used as a sample with a saturated sampling technique. The results of the study indicate that work motivation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and the work environment has a positive and significant effect on employee performance. High work motivation, good work discipline, and a conducive work environment can improve employee performance optimally.